Tinjauan Hukum Terhadap Eksistensi Waralaba Berdasarkan Peraturan Pemerintah Nomor 42 Tahun 2007 Di Indonesia - Izulkha, Ayesha Tasya; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Franchising is a business concept in which a brand owner grants a license to sell its products with the intellectual property owned by the brand under a contractual agreement. Franchise agreements include unnamed agreements, also known as innominat agreements, which are regulated outside the Civil Code. The purpose of this study is to examine more deeply the existence of the implementation of franchise agreements, as well as the form of legal protection for franchisees in Indonesia. The research method in this study is the normative juridical method. This approach is done by looking in terms of applicable laws and regulations, especially regarding the existence of franchises and their legal protection according to Government Regulation No. 42 of 2007. The results of the study reveal that the establishment of a franchise must meet the legal requirements stipulated in Article 1320 of the Civil Code, as well as the form of legal protection for franchisees listed in Article 7 of the Minister of Trade Regulation No. 12 of 2006 so that the franchisor cannot unilaterally terminate the agreement with the franchisee.